I19, the small-molecule single-crystal diffraction beamline at Diamond Light Source - Nowell, H; Barnett, SA; Christensen, K; Teat, S; Allan, DR (2012)
The dedicated small-molecule single-crystal X-ray diffraction beamline (I19) at Diamond Light Source has been operational and supporting users for over three years. I19 is a high-flux tunable-wavelength beamline and its key details are described in this article. Much of the work performed on the beamline involves structure determination from small and weakly diffracting crystals. Other experiments that have been supported to date include structural studies at high pressure, studies of metastable species, variable-temperature crystallography, studies involving gas exchange in porous materials and structural characterizations that require analysis of the diffuse scattering between Bragg reflections. A range of sample environments to facilitate crystallographic studies under non-ambient conditions are available as well as a number of options for automation. An indication of the scope of the science carried out on the beamline is provided by the range of highlights selected for this paper. © 2012 International Union of Crystallography.